Analisis Deformasi di sekitar Sesar Cimandiri Akibat Gempa Cianjur 2022 Menggunakan Data Indonesia Continuously Operating Reference Station - Fery Kurnia Sandi; Marzuki Marzuki; Vira Friska; Dwi Pujiastuti (Jurnal Fisika Unand, 2024)
The preseismic and coseismic deformation due to the 21st November Cianjur Earthquake with a magnitude of 5.6 Mw has been analyzed. This study uses Global Navigation Satellite Station (GNSS) data and 13 Indonesian Continuously Operating Reference Station (InaCORS) daily displacement data to reveal the source of the 21 November 2022 Cianjur earthquake. The InaCORS stations used include BAKO, CANG, CBTU, CJKT, CJUR, CLBG, CLDO, CPTN, CPWK, CROL, CSUM, and CUMI. This research uses GLOBK/GAMIT software and is interpreted in a deformation map. From the data processing results, the deformation pattern of station shifts in the pre-earthquake phase indicates that the movement of the Cimandiri Fault did not cause the 21 November 2022 Cianjur earthquake but was likely caused by a new fault. This is indicated by the difference between the deformation direction of the InaCORS station close to the epicenter and the direction of the Cimandiri Fault movement. The most significant horizontal coseismic deformation was obtained at 43.86 mm at CJUR station, with deformation towards the southeast. The most significant vertical coseismic deformation (uplift) was obtained at 25.9 mm at the CLDO station.